ANALISIS FAKTOR PENENTU KEBERLANJUTAN DAN STRATEGI PEMANFAATAN LAHAN DI LOKAPURNA TAMAN NASIONAL GUNUNG HALIMUN SALAK - Prasasti, Bayu Gagat; Basuni, Sambas; Sunarminto, Tutut (Media Konservasi, 2016)
Lokasi Purnawirawan (Lokapurna) is an area located in the Mount Halimun Salak National Park (TNGHS). Lokapurna is an expansion area of TNGHS through Minister of Forestry Decree No. 175 in 2003. Expansion in TNGHS caused the loss of community access to utilize the land in national park area and it caused a conflict between community and TNGHS. The determinant factor of land use sustainability in Lokapurna is important to reduce land tenure conflicts between the community and TNGHS. The conflict occur because of misperception between community and TNGHS. Moreover, the determinant factors of land use sustainability were needed to know to determine land use policy strategy in Lokapurna. This study aimed to analyze the determinant factors of land use sustainability in Lokapurna and to contrive the alternative strategies for land use in Lokapurna. This research method using qualitative methods. The selection of respondents were conducted by purposive sampling with consideration of respondents who are involved directly or deemed to have the ability and understanding regarding land use in Lokapurna. The research data was obtained through closed ended questionnaire. This data was analyzed by analytic hierarchy process (AHP) method and processed using software Expert Choice 2000. The result shown that the highest determinant factor of land use sustainability in Lokapurna is environmental factors (0,472) followed by social factors (0,301) and economic factors (0,272). Moreover, the first priority of alternative land use strategy is collaborative ecotourism development (0,494), the second priority is the optimization of specific zone (0,378) and the last priority is community relocation (0,124). Keywords: land use, Lokapurna, Mount Halimun Salak National Park, priority, strategy